Optimization of pGEX System to Express and Isolate Mycobacterium tuberculosis Inclusion Body Protein in Combining with Modified Refolding Method - Rukmana, Andriansjah; Burhanuddin, Burhanuddin; Yasmon, Andi (Makara Journal of Science, 2018)
Antigen sub units for vaccine studies are typically isolated from recombinant proteins in an expression system. However, not all protein expression systems are used to express the specific protein. In this study,we optimized the pGEX system combined with the modified protein refolding to express and isolate M. tuberculosis proteins, especially proteins that are expressed as an inclusion body. Resuscitation promoting factor B (RpfB) protein is one of the Resuscitation promoting factor (Rpf) family of proteins that has been studied for its ability to induce cellular immunity in animal tests. Silico analyses demonstrate how RpfB is included in cell wall and cell processes. The Rpf family proteins are promising antigens that can be used as a TB vaccine candidate. The polymerase chain reaction was briefly performed using specific primers to amplify the full length of the rpfB. PCR amplification products were then purified, cut by restriction endonucleases, and cloned into pGEX 6-P1. Protein expression was done in the Escherichia coli BL21 strain, and expressed protein was isolated using themodified protein refolding and solubilization method. The complex protein expression that appeared as inclusion bodies were successfully isolated and can be detected as complex GST-RpfB through the western blotting process. Our study results indicate that this system and our modified method are suitable for M. tuberculosis inclusion body protein expression and isolation.